Exploring the role of perfectionism and psychological capital in the relationship between academic procrastination, test anxiety and suicidal ideation among pre-medical students - Dongzi Zhang; Iqra Mushtaque; Muhammad Wasif Hanif (Acta Psychologica)
The present study explores the direct, mediating and moderating effects of perfectionism and psychological capital on the relationship between academic procrastination, test anxiety and suicidal ideation among pre medical students in Pakistan. Data was collected using a quantitative, cross-sectional research design from 920 participants attending entrance test centers in Lahore and Multan, recruited through convenience sampling. A structured self-administered questionnaire was completed by participants. Correlations, mediation and moderation effects were assessed using SPSS and the PROCESS macro. Results show a highly significant direct effect of academic procrastination and test anxiety on suicidal ideation, both of which increase students' suicidal thoughts. We found a mediating role of perfectionism whereby high perfectionistic tendencies amplified the relationship between academic procrastination and test anxiety leading to a higher likelihood of suicidal ideation. Furthermore, psychological capital was found to moderate the effect of test anxiety on suicidal ideation. These results suggest that there is a necessity of the development of interventions aiming at reduction of the indirect impact of academic procrastination on the students' psychological well-being by altering the psychological mediators. Educational institutions should begin to introduce programs revolving stress management and promotion of mental health to assist students to cope with stress, academic procrastination and perfectionism.